Trust Deficit Vs. Trade Deficit: An Analysis of Misconceptions towards Indo-Pakistan Trade Relations - Asfandiyar Khan; Nimra Malik; Anum Jafar; Parwanat Khan, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
This study explores that history of trade relations between Pakistan and India which have been dominated by three perspectives. First and common (Indian) point of view is that there should be no trade between Pakistan and India. It is based on assumptions that Pakistan is an enemy state therefore, India should not benefit their economy. The second misperception is that trade with India would dump Pakistani market thus challenging local industries if trade is open (Pakistan’s perspective). The third perspective, which advocates a careful budding up of trade activities between both the states. Since independence, discrepant trade agreements and policies of both the countries have induced constant reversal in the advancement and accomplishment of further developing trade relations. So, in this type of situation any positive step toward peace, stability and prosperity is seen with suspicion. The study has been constructed using the lens of constructivism. India-Pakistan relations are socially constructed. Most of the data presented is primary in nature, for the data analysis NVIVO software has been used. It is need of the hour, not to create trade balance in the region keeping the world scenarios - changing from geopolitics to geo-economics.